Small farmers' preferences for the design of certification schemes: Does gender matter? - Eva-Marie Meemken; Prakashan Chellattan Veettil; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2016)
Farmers' preferences for sustainability certification are analyzed, building on a choice experiment conducted with smallholder coffee growers in Uganda. Farmers have positive general attitudes towards certification. While they dislike bans of productivity-enhancing inputs, benefits associated with agricultural training and special female support are appreciated. Many also see requirements that have to be met for certification as a welcome nudge to invest in better farm management and quality upgrading. Gender-disaggregated data reveal that female farmers have a higher preference for sustainability certification than male farmers. Also within households, significant preference heterogeneity between males and females is found for some certification attributes.
Keywords: Q01; Q12; Q13; Q18; 330; choice experiment; farmer preferences; food standards; gender; mixed logit models